PELAKSANAAN PROYEK OPERASI NASIONAL AGRARIA PADA KANTOR BADAN PERTANAHAN NASIONAL KABUPATEN MAMUJU - Munawir Arifin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims To obtain a description of the Implementation of National Agrarian Operations Project At the National Land Agency Office of Mamuju Regency Type of research used is descriptive. Data collection was done using field research (field research), library research and data tracking on line. The data obtained are then analyzed qualitatively by explaining or describing the data being studied or obtained from the field, both primary data obtained from the interviews, as well as from secondary data. The results of this study indicate that the National Agrarian Operations Project Implementation at the National Land Office of Mamuju Regency has not run optimally due to the lack of proactive community to come directly to the land office to ask what matters are the requirements to take care of the land deed.